REPOSISI PERANAN DAN FUNGSI PERPUSTAKAAN MASJID DALAM MENCERDASKAN UMAT ISLAM - Effendi, M Nur (Jurnal El-Pustaka, 2020)
Masjid (Mosque) is not only used as a place of praying, but also becomes a social institution that has a role in the development of education, economics, and politics of the people. The mosque has many functions; one of them is as an educational institution. As an educational institution, the mosque cannot be separated from the existence of libraries. The Library of mosques is one form of a special library that serves the intellectual needs of the surrounding community. With the library, the mosque also serves as a center of education because through the library of the mosques and Muslims generally learn anything that has been produced first and always be able to follow and adapt to new information positively. The main role that must be done by the mosque’s library is to realize the society that aware of information and know-how to obtain and use information properly. With a good collection of library management and services, it will bring information-awareness to people to appreciate the science more than just information.